Perancangan Jaringan Internet Menggunakan GNS3, Qemu, dan Virtual Box - Amantha Olan Sahat Manik, Lukas; Ghozali, Theresia; Windha Mahyastuty, Veronica (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
In the modern era, information technology continues to develop in line with human needs who want efficiency, ease, speed and accuracy in obtaining information and sending information. Moreover, in an office building, facilities for accessing information require a fast and efficient internet network as facilities and infrastructure to support office activities. In general, Mikrotik routers are widely used in office buildings as a means of distributing the internet. With the use of a mikrotik router that requires a lot of design and simulation first to get good internet performance GNS3 can design a topology that will be used in 2 ways, namely using Qemu and Virtual Box. Both of these methods have their respective advantages over the design process and test results